2022
DOI: 10.1021/acs.jpca.2c00495
|View full text |Cite
|
Sign up to set email alerts
|

Diabatic Valence-Hole States in the C2 Molecule: “Putting Humpty Dumpty Together Again”

Abstract: Despite the long history of spectroscopic studies of the C2 molecule, fundamental questions about its chemical bonding are still being hotly debated. The complex electronic structure of C2 is a consequence of its dense manifold of near-degenerate, low-lying electronic states. A global multi-state diabatic model is proposed here to disentangle the numerous configuration interactions that occur within four symmetry manifolds of excited states of C2 (1Πg, 3Πg, 1Σ u + , and 3Σ u + ). The key concept of our model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…The Deslandres-d'Azambuja C 1 Π g − A 1 Π u and Messerle-Krauss C ′ 1 Π g − A 1 Π u bands were only observed in very early studies [29][30][31][32]. However, recent calculations suggested that the Messerle-Krauss band is actually a part of the Deslandres-d'Azambuja band [11,33], which is also verified by our calculation here. Among the three 3 Π u states in this region, the e 3 Π g state was discovered early [34,35].…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…The Deslandres-d'Azambuja C 1 Π g − A 1 Π u and Messerle-Krauss C ′ 1 Π g − A 1 Π u bands were only observed in very early studies [29][30][31][32]. However, recent calculations suggested that the Messerle-Krauss band is actually a part of the Deslandres-d'Azambuja band [11,33], which is also verified by our calculation here. Among the three 3 Π u states in this region, the e 3 Π g state was discovered early [34,35].…”
Section: Introductionsupporting
confidence: 88%
“…The C 1 Π g state has a notable avoided crossing with 2 1 Π g , which has been well described by a diabatic valence-hole model. [33] The adiabatic D 1 Σ + u state has an avoided crossing with the adiabatic 2 1 Σ + u state at R = 1.75 Å. From the shape of the two adiabatic curves, the diabatic 2 1 Σ + u state in this region has a potential well around R = 1.90 Å, which is very close to the avoided crossing point.…”
Section: Low-lying Statesmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition to the important applications relevant in astrochemistry, the bonding nature of C 2 in its ground electronic state has long been a challenging while at the same time interesting topic in the study of chemical bonding. There have been substantial debates about whether C 2 has a real quadruple bond in its ground electronic state. Because of its relevance in astrochemistry and chemical bonding, spectroscopic research on C 2 has a history spanning more than two centuries, and it remains a subject of significant current experimental and theoretical interest. , …”
mentioning
confidence: 99%
“…In the recent work by Jiang et al, it was shown that the previously neglected valence-hole states, which intrinsically have large binding energy and correlated with high lying atomic fragment channels, can lead to large and systematic disruptions to the highly excited electronic states of C 2 . 17 Π g and 1,3 Σ u + and thus should not significantly perturb the 3 3 Δ g state here.…”
Section: Resultsmentioning
confidence: 84%